2012
DOI: 10.1128/cvi.00300-12
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Heterogeneity in the Atypical Group of Novel Emerging Brucella Species

Abstract: ABSTRACTRecently, novelBrucellastrains with phenotypic characteristics that were atypical for strains belonging to the genusBrucellahave been reported. Phenotypically many of these strains were initially misidentified asOchrobactrumspp. Two novel species have been describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
4
29
0
Order By: Relevance
“…Furthermore, during the last decade, Brucella has been identified as a pathogen of several marine mammals, and MAb reactivity patterns almost identical to that described here for B. suis biovar 2 have been reported for B. ceti strains isolated from some dolphin species [28]. Also, like B. suis biovar 2, several Brucella strains isolated from wild rodents in Australia do not react with MAb of C and M specificities [29]. Thus, it seems that the A-positive, C and M-negative epitopic structure is not infrequent outside the B. abortus and B. melitensis clusters and that it represents a new and extended Brucella serovar.…”
Section: Resultssupporting
confidence: 73%
“…Furthermore, during the last decade, Brucella has been identified as a pathogen of several marine mammals, and MAb reactivity patterns almost identical to that described here for B. suis biovar 2 have been reported for B. ceti strains isolated from some dolphin species [28]. Also, like B. suis biovar 2, several Brucella strains isolated from wild rodents in Australia do not react with MAb of C and M specificities [29]. Thus, it seems that the A-positive, C and M-negative epitopic structure is not infrequent outside the B. abortus and B. melitensis clusters and that it represents a new and extended Brucella serovar.…”
Section: Resultssupporting
confidence: 73%
“…This is likely related to the composition of LPS in the classical species that differs from the conventional LPS structure found in other gram(-) bacterial pathogens (Cardoso et al, 2006). In this regard, it has been shown that the core-lipid A moiety of LPS of B. microti is different from classical Brucella spp., although its ability to activate TLR4 has not been tested yet (Zygmunt et al, 2012). Further supporting this hypothesis, it is well known that TLR2 and TLR4 are crucial in host defense against several bacterial pathogens that, like B. microti , cause sepsis like Staphylococcus aureus, Streptococcus pneumoniae (Takeuchi et al, 2000; Dessing et al, 2008), Klebsiella pneumoniae (Schurr et al, 2005), Haemophillus influenza (Wang et al, 2002) and Acinetobacter baumanii (Knapp et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the same occurred for the B. suis 145 extracellular fraction in that some of its LPS resisted acid-heat hydrolysis, protecting a PS antigen that provided additional vaccine efficacy. Such an antigen could be a different A or M antigen similar to different A antigens observed for B. abortus and Yersinia enterocolitica O:9 (25), an additional "soluble supernatant substance" or "S antigen" proposed by researchers in the 1930s (26), or more recently the reported novel PS antigens of B. suis (27,28). These possibilities could also explain how CE showed that anti-A, anti-M, and anti-A/M/C monoclonal antibodies bound to cell-associated PS fractions B2 and B3 but not the extracellular fraction B1 and how the subunit vaccine fractionated by pH had the two most effective fractions at the lowest and highest pI.…”
Section: Discussionmentioning
confidence: 96%